An investigation of oxidant/antioxidant balance in patients with migraine: a case-control study - Togha, Mansoureh (BMC Neurol, 2019)
BACKGROUND: In recent years, the role of neuroinflammation and oxidative stress in migraine pathogenesis has achieved considerable interest; however, to date findings are equivocal. Thus, the objective of this study was to investigate biomarkers of oxidative stress in episodic and chronic migraineurs (EM and CM patients) and controls. METHODS: Forty-four patients with EM, 27 individuals with CM and 19 age-sex-matched controls were enrolled. After collecting data on demographic and headache characteristics, blood samples were collected and analyzed to detect serum levels of oxidative stress biomarkers (malondialdehyde (MDA) and nitric oxide (NO)); total antioxidant capacity using Trolox equivalent antioxidant capacity (TEAC) assay; and antioxidant enzymes (catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase-1 (GPx-1)). RESULTS: Serum levels of CAT and SOD were significantly lower in the CM group than the EM group and controls. However, serum GPx-1 levels of the CM patients were slightly higher than the EM patients and controls (P-value≤0.001). CM patients had lower mean TEAC values than EM patients and controls. In addition, serum levels of NO and MDA were significantly elevated among subjects with CM compared to EM and control individuals (P-value≤0.001). Pearson correlation analysis revealed negative correlations between the number of days of having headaches per month and serum concentrations of the two antioxidant enzymes CAT (r = − 0.60, P-value< 0.001) and SOD (r = − 0.50, P-value< 0.001) as well as TEAC values (r = − 0.61, P-value< 0.001); however, there were positive correlations between headache days and serum GPx-1 levels (r = 0.46, P-value< 0.001), NO (r = 0.62, P-value< 0.001), and MDA (r = 0.64, P-value< 0.001). CONCLUSION: Present findings highlighted that chronic migraineurs had lower total non-enzymatic antioxidant capacity and higher oxidative stress than episodic migraineurs and control individuals. Although more studies are needed to confirm these data, applying novel prophylactic medications or dietary supplements with antioxidant properties could be promising in migraine therapy.